PEMANFAATAN TELAJAKAN/RUANG TERBUKA HIJAU DAN TABULAMPOT UNTUK PRODUKSI ECO ENZYME: PERHITUNGAN BIAYA STRATEGI PEMASARAN MELALUI E-COMMERCE MENGGUNAKAN PENDEKATAN MATEMATIKA - Ni Wayan Dian Permana Dewi; I Made Sudiana; I Made Agus Widiana Putra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service program aims to empower the Subak Sidang Rapuh Farmers Group in Marga Dauh Puri Village, Tabanan Regency, through the utilization of Telajakan (traditional Balinese green open spaces) and Tabulampot (fruit plants in pots) for Eco Enzyme production. The main problems faced by farmers include underutilized land, high dependency on chemical pesticides, and limited understanding of cost management and digital marketing. The program’s solutions include training on tabulampot cultivation and Eco Enzyme production, cost calculation using mathematical approaches, and marketing strategies through e-commerce platforms. The results showed significant improvements in farmers’ knowledge and skills—100% of participants successfully managed telajakan as productive land, produced Eco Enzyme independently, and understood the fundamentals of cost calculation and digital marketing. This program has proven effective in promoting sustainable agriculture, reducing organic waste, and increasing community income based on Balinese local wisdom.